Individual and environmental factors influencing adolescents’ dietary behavior in low- and middle-income settings - Verstraeten, Roosmarijn; Leroy, Jef L.; Pieniak, Zuzanna; Ochoa-Avilés, Angélica; Holdsworth, Michelle; Verbeke, Wim; Maes, Lea; Kolsteren, Patrick (Public Library of Science, 2016)
Objective: Given the public health importance of improving dietary behavior in chronic disease prevention in low- and middle-income countries it is crucial to understand the factors influencing dietary behavior in these settings. This study tested the validity of a conceptual framework linking individual and environmental factors to dietary behavior among Ecuadorian adolescents aged 10–16 years.